Brown Flaxseed Prevents DNA Damage Induced by 1,2-Dimethylhydrazine in a Pre-Clinical Model - Maria Tereza Pamplona-Silva; Walter Vinicius Morandi; Luana Bernardi; Bethânia Borges Tura; Diego Duarte Marques de Oliveira; Andreia Conceição Milan Brochado Antoniolli-Silva; Mariana de Oliveira Mauro; Rodrigo Oliveira (Brazilian Archives of Biology and Technology, 2018)
ABSTRACT The study evaluated the effects of brown flaxseed supplementation in natura on the prevention of DNA damage induced by 1,2-dimethylhydrazine (DMH) in vivo. The experimental groups were Negative and Positive Controls and the protocols of Pre-treatment, Simultaneous, Post-treatment, Pre+continuous in relation to the supplementation of brown flaxseed and administration with carcinogenic compound. The results showed that brown flaxseed supplementation does not cause genomic and genetic damage. In addition, brown flaxseed showed a chemopreventive food that reduced the damages assessed by the comet assay up to 94.07x and the damages assessed by the micronucleus assay up to 91.88x. Brown flaxseed supplementation also increased the frequency of monocytes and lymphocytes indicating immunological improvements. Thus, brown flaxseed supplementation is considered safe and reduces the frequency of DNA damage that can lead to tumors. Therefore, if these events are confirmed in humans, flaxseed will have reinforced its indication as a functional chemopreventive food in the prevention of cancer.